Transformational Leadership, Innovative Climate, and Employee Creativity in Rattan Craftsmen MSMEs - Haris Kristian (Jurnal Manajemen Sains dan Organisasi, 2025)
Objective – This research aims to provide an empirical explanation of the influence of transformational leadership on employee creativity with an innovative climate as an intervening variable.Design/Methodology/Approach – This research method is a descriptive-quantitative research approach. The research location was 6 (six) MSME Rattan Craftsmen in Palangka Raya City, totaling 71 people, with the sampling technique used being a saturated sampling technique. The collected data was analyzed using the Structural Equation Modeling (SEM) approach with the Partial Least Square (PLS) approach. The software used was SmartPLS 3.3.3.Findings – The research results show that Transformational Leadership has a positive and significant effect on Employee Creativity, Transformational Leadership has a positive and significant effect on Innovative Climate, Innovative Climate has a positive and significant effect on Employee Creativity, Innovative Climate is able to act as an intervening in the relationship between Transformational Leadership and Employee Creativity.Implications – The leadership of UMKM Rattan Craftsmen in Palangka Raya City can hold discussions to stimulate new ideas, then provide recognition and rewards for creative contributions. Leaders can also model creative thinking and innovation as leaders, and ensure employees have the resources they need to realize their ideas.